A retrospective study on endometrial patterns in abnormal uterine bleeding - M., Priya; Anuradha, C. R.; Raghavan, Vijayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To determine the type of endometrial patterns of the different age categories of women who presented as a case of abnormal uterine bleeding. Methods: This is a retrospective study conducted on 105 patients who presented with abnormal uterine bleeding who underwent fractional curettage in our hospital. The data on their age, presenting complaints, and comorbidities of all the women were collected. The patterns of endometrial changes were studied and classified. Results: The most common histopathological findings were anovulatory shedding (34.3%) and irregular shedding (18.1%). The other findings include irregular ripening, papillary endocervicitis, endocervicitis, pill endometrium, atrophic endometrium, squamous metaplasia, and endometrial hyperplasia. The most common malignant change seen was endometrioid carcinoma which was seen in women over 40 years of age. Conclusions: Histopathological examination of the endometrium shows a clear-cut differentiation between physiological and malignancy changes in the endometrium. Hence, endometrial sampling is considered the golden tool for accurate analysis of the endometrium.